Cost-Utility of Cognitive Behavioral Therapy for Low Back Pain From the Commercial Payer Perspective. Issue 10 (15th May 2015) - Norton, Giulia; McDonough, Christine M.; Cabral, Howard; Shwartz, Michael; Burgess, James F.
<x xml:space="preserve">Abstract</x> Study Design. Markov cost-utility model. Objective. To evaluate the cost-utility of cognitive behavioral therapy (CBT) for the treatment of persistent nonspecific low back pain (LBP) from the perspective of US commercial payers. Summary of Background Data. CBT is widely deemed clinically effective for LBP treatment. The evidence is suggestive of cost-effectiveness. Methods. We constructed and validated a Markov intention-to-treat model to estimate the cost-utility of CBT, with 1-year and 10-year time horizons. We applied likelihood of improvement and utilities from a randomized controlled trial assessing CBT to treat LBP. The trial randomized subjects to treatment but subjects freely sought health care services. We derived the cost of equivalent rates and types of services from US commercial claims for LBP for a similar population. For the 10-year estimates, we derived recurrence rates from the literature. The base case included medical and pharmaceutical services and assumed gradual loss of skill in applying CBT techniques. Sensitivity analyses assessed the distribution of service utilization, utility values, and rate of LBP recurrence. We compared health plan designs. Results are based on 5000 iterations of each model and expressed as an incremental cost per quality-adjusted life-year. Results. The incremental cost-utility of CBT was $7197 per quality-adjusted life-year in the first year and $5855 per quality-adjusted life-year over 10 years. The results are robust across numerous sensitivity analyses. No change of parameter estimate resulted in a difference of more than 7% from the base case for either time horizon. Including chiropractic and/or acupuncture care did not substantively affect cost-effectiveness. The model with medical but no pharmaceutical costs was more cost-effective ($5238 for 1 yr and $3849 for 10 yr). Conclusion. CBT is a cost-effective approach to manage chronic LBP among commercial health plans members. Cost-effectiveness is demonstrated for multiple plan designs. Level of Evidence: 2